Pendampingan Manajemen Tatakelola Gula Jawa Jahe Familo Dukuh Ragayudan RT 02 RW 02 Desa Bocor Kecamatan Bulus Pesantren Kebumen Jawa Tengah - Rahmadi Yotenka; Muhaimin Muhaimin; Muhammad Muhajir (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
This community service aims to improve the management and governance of the home industry of Familo's Ginger Javanese Sugar through training and mentoring marketing management with e-commerce systems. The program of community service activities is carried out through several stages, namely the preparatory stage, the implementation stage, and the evaluation stage. The results achieved through this activity are participants be able to market their products by e-commerce system optimally.